Synergy of tectonic geomorphology, applied geophysics and remote sensing techniques reveal the existence of active tectonism in NW Peloponnese (Greece) - Fountoulis, I.; Vassilakis, E; Mavroulis, S.; Alexopoulos, J.; Dilalos, S.; Erkeki, A. (Geomorphology, 2015)
In tectonically active areas, such as in the northwest Peloponnese of western Greece, geomorphic processes are strongly influenced by active faulting; in many cases such faults cannot be easily identified. In this paper we apply multidisciplinary analysis (morphotectonic indices, neotectonic mapping, geophysical surveys and remote sensing techniques) to map the recently-recognized east–west trending Pineios River normal fault zone with a high degree of accuracy, and to better understand its contribution to the evolution of the ancient region of Elis during Holocene time. Fault activity seems to be related to frequent changes in river flow patterns and to displacements of the nearby shoreline. We argue that fault activity is the main reason for migration of Pineios river mouth as documented for several time periods during historical time. Quantitative constraints on deformation caused by the faulting were applied through the application of the morphotectonic indices proposed in this paper, including drainage network asymmetry and sinuosity, and mountain front sinuosity, all of which indicate that this is a highly active structure. Slip rates calculated to be as high as 0.48 mm/yr for the last 209 ka (based on previously published dating) were verified by applied geophysical methods. The fault surface discontinuity was identified at depth using vertical electrical resistivity measurements and depositional layers of different resistivity were found to be clearly offset. Displacement increases toward the west, reaching an observed maximum of 110 m. The most spectacular landform alteration due to surface deformation is the north–south migration of the river estuary into completely different open sea areas during the late Quaternary, mainly during the Holocene. The sediment transport path has been altered several times due to these changes in river geometry with and the most recent seeming to have occurred almost 2000 years ago. The river estuary migrated to its contemporary position along the southern coast, settled on the hanging wall, inducing retrograding of the northern coast, and settled on the foot wall, with rates reaching the order of 0.52 m/yr, as concluded from historical and recently-acquired remote sensing data.